Miaka Hamsini ya Kiswahili Nchini Kenya - Simala, Inyani (Book collections on Project MUSE., 2014)
Fifty Years of Kiswahili in Kenya is a collection of articles that were presented at an international Kiswahili conference organized by the National Kiswahili Association (CHAKITA) Kenya in 2013, which was held at the Catholic University of Eastern Africa (CUEA). A few articles are however from a similar conference held in 2012 at Kenyatta University. The book exemplifies the importance of the Kiswahili language in various sectors of society. Therefore, within this book you will find articles that focus on the teaching of the Kiswahili language; Kiswahili as a tool for national economic develo.